Exploring Energy Transition-Longevity Nexus in Developing Countries Vulnerable to Climate Change - Kamalu, Kabiru; Binti Wan Ibrahim, Wan Hakimah (Ekonomika, 2026)
One of the topical global challenges that jeopardises achieving sustainable future is the increasing carbon emission from many developing countries due to poor environmental regulations, resources shortages and inadequate clean technology to derive an energy transition process, which reduces longevity. This study examines the effect of energy transition on life expectancy in low and lower-middle income developing countries heavily affected by numerous environmental calamities due to weak institutions and resource shortage. Also, the study examines the moderating role of institutional quality and income growth on the energy transition-longevity nexus. This study uses the Cross Section Autoregressive Distributive Lag (CS-ARDL) estimator, and the Dynamic Common Correlated Effect (DCCE) as a robust estimator. The study uses data from 60 countries, with available data from 1996 to 2022. The findings revealed that energy transition promotes an increase in life expectancy; higher institutional quality and income growth significantly enhance the positive effect of energy transition on longevity in the selected developing countries. The results from the robust estimator confirmed our result, except for the magnitude of the coefficients being higher in the CS-ARDL estimator. To increase the life expectancy in developing countries, policymakers should adopt energy transition wholistically as an important policy option so that to reduce environmental pollution and achieve a higher life expectancy.
Keywords: Renewable energy; Air pollution; Longevity; Sustainability